Synthesis of optically pure 2,3,4-trisubstituted tetrahydrofurans via a two-step sequential Michael-Evans aldol cyclization strategy: total synthesis of (+)-magnolone - Pandey, Ganesh; Luckorse, Srikanth; Budakoti, Asha; Puranik, Vedavati G. (Tetrahedron Letters, 2010)
Synthesis of optically pure 2,3,4-trisubstituted tetrahydrofurans is described employing a two-step Michael-Evans aldol cyclization strategy. The approach is successfully applied for the total synthesis of furano lignan natural product (+)-magnolone. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: HWE reaction; Lignans; Magnolone; Michael-Evans aldol reaction; Tetrahydrofuran